Independent Impact of Peripheral Artery Disease on Percutaneous Coronary Intervention - Leor Perl; Tamir Bental; Hana Vaknin‐Assa; Abid Assali; Pablo Codner; Yeela Talmor‐Barkan; Gabriel Greenberg; Abed Samara; Guy Witberg; Katia Orvin; Ran Kornowski (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2020)
Background Peripheral artery disease (PAD) is a known risk factor for adverse outcomes in patients undergoing percutaneous coronary intervention. However, in some studies PAD is not an independent risk factor. We sought to examine the independent impact of PAD on a large prospective percutaneous coronary intervention registry. Methods and Results From our single‐center prospective percutaneous coronary intervention registry, we have retrospectively analyzed 25 690 patients (years 2004–2018). We examined the influence of PAD on short‐ and long‐term outcomes using both regression and propensity‐matched analyses. Patients with documented PAD (n=1610, 6.3% of total) were older (66.7±10.8 versus 65.4±12.1, P<0.01), had higher rates of diabetes mellitus (69.3% versus 46.3%, P<0.01), hypertension (92.1% versus 76.1%, P<0.01) and renal failure (38.3% versus 18.2%, P<0.01). There were no differences in the rates of stable versus acute presentations, but less were treated with Prasugrel and Ticagrelor (3.3% versus 8.0% and 7.9% versus 11.9%, respectively, P<0.001 for both). Both 30‐day and 3‐year rates of all‐cause death and major adverse cardiac events were higher for patients with PAD versus control (4.9% versus 2.1% and 7.3% versus 3.3% death and major adverse cardiac events at 30 days, respectively; 43.4% versus 29.0% and 55.0% versus 37.8%, respectively at 3 years, P<0.001 for all). Following multivariate analysis, the presence of PAD was associated with a higher risk of both death (hazard ratio [HR], 1.66; CI 1.52–1.83; P<0.001) and major adverse cardiac events (HR, 1.51; CI, 1.40–1.64; P<0.001). Conclusions PAD constitutes an independent risk factor for adverse outcomes in patients undergoing percutaneous coronary intervention. Further studies are needed to ascertain which effective therapies may mitigate this risk.